DIVERSION PRACTICES IN JUVENILE TRAFFIC CRIME INVESTIGATIONS AS A SOCIAL ENGINEERING TOOL: A CASE IN NORTH MALUKU, INDONESIA - Abdulajid, Syawal; Anshar, Anshar; Mufti, Ahmad; Suwito, Suwito (Cepalo, 2024)
Diversion as an alternative to out-of-court settlement faced both theoretical and practical challenges. In the context of traffic offenses committed by minors, the practice of diversion encountered legal uncertainties about whether it could effectively address the core issues. The dilemma arose from the need to enforce the law while also protecting the rights of children as mandated by the Juvenile Justice System Law. This paper reviewed the practice of diversion in resolving traffic offenses by minors in North Maluku, aiming to assess its effectiveness and explore its role as a tool of social engineering. The research employed a doctrinal legal research model with a juridical-normative approach. Findings indicated that diversion practices in North Maluku, particularly for traffic offenses committed by minors, were ineffective due to several factors: regulatory deficiencies, lack of competence among enforcement personnel, and the prevailing legal paradigm within the community. From the perspective of law as a tool of social engineering, diversion alone was insufficient without subsequent measures to address traffic crimes committed by minors, necessitating the reconstruction of the legal culture and enhancement of public awareness to foster traffic order and safety.